2022
DOI: 10.1093/nar/gkac1180
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring translation in all reading frames downstream of weak stop codons provides mechanistic insights into the impact of nucleotide and cellular contexts

Abstract: A stop codon entering the ribosome A-site is normally decoded by release factors that induce release of the polypeptide. Certain factors influence the efficiency of the termination which is in competition with elongation in either the same (readthrough) or an alternative (frameshifting) reading frame. To gain insight into the competition between these processes, we monitored translation in parallel from all three reading frames downstream of stop codons while changing the nucleotide context of termination site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…A previous study showed that Gly acts as a C-terminal degron and is rarely found at the C-terminal end of the normal proteome, suggesting one possible biological basis for Gly-PTC enrichment (28,29). It is also possible that Gly-PTC stimulates PTC readthrough, leading to NMD escape and some functionality of the protein product (30), or that Gly-PTC enhances NMD and elimination of the mRNA transcript.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that Gly acts as a C-terminal degron and is rarely found at the C-terminal end of the normal proteome, suggesting one possible biological basis for Gly-PTC enrichment (28,29). It is also possible that Gly-PTC stimulates PTC readthrough, leading to NMD escape and some functionality of the protein product (30), or that Gly-PTC enhances NMD and elimination of the mRNA transcript.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that Gly acts as a C-terminal degron and is rarely found at the C-terminal end of the normal proteome, suggesting that Gly-PTC enrichment in non-essential genes may be due to efficient Gly-end truncated protein degradation (Koren et al, 2018; Lin et al, 2018). It is also possible that Gly-PTC stimulates PTC readthrough, leading to NMD escape and some functionality of the protein product (Loughran et al, 2023), or that Gly-PTC enhances NMD and elimination of the mRNA transcript. Readthrough would confer a benefit to the organism as it would preserve gene function, while elimination of the truncated protein or encoding transcript might have a neutral effect if the gene is otherwise non-essential.…”
Section: Resultsmentioning
confidence: 99%
“…Both bear UGA stop codons which are generally most prone to TR [ 25 27 ]. The MeCP2 p.R198X variant further contains a cytosine in the + 4 SCC position which was previously shown to additionally increase the TR efficiency [ 26 , 45 ]. Further, p.R198X was the only variant that expressed the full-length MeCP2 isoform confirming the high basal TR of the UGA C context.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the +4 position, the sequence influence seems to diminish but some effect is still exerted by nucleotides as far out as +9 . While no common consensus sequence has emerged, there is some evidence of eukaryotic sequences that bias NTC readthrough, e.g., UGA-CUAG in Drosophila , or various sequences that support viral readthrough and may enhance aminoglycoside activity , The impact of the 5′ sequence context is less well established but some studies have shown that an adenine at the −1 position may improve readthrough rates. …”
Section: Nonsense Suppressor Trnas Read Through Premature Stop Codons...mentioning
confidence: 99%